2003
DOI: 10.2355/isijinternational.43.907
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Computation for the Melt Convection of the Model System of Continuous Steel Casting with Various Magnetic Fields

Abstract: Melt flow in the model system of continuous steel casting process was numerically computed with an application of various magnetic fields. The model geometry is 1ϫ1ϫ2 which is not in accordance with the current shape employed in a practical industry. Electric coil to produce a magnetic field was either vertical, horizontal and parallel, or perpendicular to the nozzle jet from the tandish. Detailed melt flow in the mold is graphically presented. The axial magnetic field appears to suppress the jet flow most eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Various new phenomena related to magnetoaerodynamic and magnetohydrodynamic have been reported for example airflow generation [6], promotion of combustion [7] or magnetic levitation of water [8]. The magnetic field has also been employed for various industrial purposes like Czochralski method in crystal growth [9], continuous steel casting [10] or liquid metal cooling blankets for fusion reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Various new phenomena related to magnetoaerodynamic and magnetohydrodynamic have been reported for example airflow generation [6], promotion of combustion [7] or magnetic levitation of water [8]. The magnetic field has also been employed for various industrial purposes like Czochralski method in crystal growth [9], continuous steel casting [10] or liquid metal cooling blankets for fusion reactors.…”
Section: Introductionmentioning
confidence: 99%
“…The development of superconducting magnets has made the application of a magnetic field possible even on an industrial scale. Phenomena related to the magnetic field and the magnetic buoyancy force have found applications in medicine [7], chemistry [8], physics [9], engineering [10,11], and other areas.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that when the Seebeck effect operates, an additional current is induced spontaneously from the cold wall to the hot wall in the liquid metal. Ezaki et al [11] studied melt flow in the model system of the continuous steel casting process with an application of various magnetic field directions numerically. Three different coil locations were considered to have X-, Y-, or Z-directional magnetic fields.…”
Section: Introductionmentioning
confidence: 99%